Toward an Entrepreneurial Ecosystem Research Program - Wurth, Bernd; Stam, Erik; Spigel, Ben (Entrepreneurship Theory and Practice, 2022)
Entrepreneurial ecosystems have become a prominent concept, yet in its current state, the concept itself represents a paradox. While it draws on a rich intellectual history and provides an opportunity to synthesize different strands of research, it is also under-theorized and the mechanisms that govern ecosystem evolution are not well understood. This paper takes stock of recent advancements in ecosystem scholarship and synthesizes the empirical reality of the causal mechanisms. We use these dynamics to position ecosystems in a broader context, within and beyond the domain of entrepreneurship research, and propose a transdisciplinary research program for ecosystem research and practice.